2005
DOI: 10.1104/pp.104.057836
|View full text |Cite
|
Sign up to set email alerts
|

Localized Hormone Fluxes and Early Haustorium Development in the Hemiparasitic Plant Triphysaria versicolor

Abstract: Perhaps the most obvious phenotypes associated with chemical signaling between plants are manifested by parasitic species of Orobanchaceae. The development of haustoria, invasive root structures that allow hemiparasitic plants to transition from autotrophic to heterotrophic growth, is rapid, highly synchronous, and readily observed in vitro. Haustorium development is initiated in aseptic roots of the facultative parasite Triphysaria versicolor when exposed to phenolic molecules associated with host root exudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…The general up-regulations of genes associated with nutrient metabolism and transport are consistent with the principal function of the haustorium: tapping host resources. The regulated flux of auxins and cytokinins is probably the most expected of a developmental transition and consistent with previous studies of haustorial organogenesis [22].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The general up-regulations of genes associated with nutrient metabolism and transport are consistent with the principal function of the haustorium: tapping host resources. The regulated flux of auxins and cytokinins is probably the most expected of a developmental transition and consistent with previous studies of haustorial organogenesis [22].…”
Section: Discussionsupporting
confidence: 77%
“…A role for auxin at this early time point is also consistent with the arrest of root elongation observed upon DMBQ exposure prior to commitment. Phytohormone studies in T. versicolor have also implicated a role for auxin signaling in haustorial organogenesis [22]. As cytokinins induce haustorium development, the developmental transition may also be regulated by both of these often antagonistic hormones [11].…”
Section: Difference Library Construction and Analysis Of Regulated Genesmentioning
confidence: 99%
“…Polar auxin accumulation has been postulated as a universal feature of early plant organogenesis, and localized auxin accumulation has been shown to be required for early haustorium development in T. versicolor (Benková et al, 2003;Tomilov et al, 2005). An increased activity of genes underlying polar auxin transport in dodder infective stages likely establishes auxin maxima that induce haustoria formation.…”
Section: Phytohormone Activity In Dodder Development and Parasitismmentioning
confidence: 99%
“…In the aseptic roots of the facultative parasite Triphysaria versicolor, haustorial development can be initiated by exposing the roots to phenolic derivatives exuded by the hosts' roots (Albrecht et al, 1999). Tomilov et al (2005) identified the accumulation of auxin and ethylene as early events in haustorium development of the hemiparasitic plant T. versicolor. S. album seeds pretreated with 2-8 mM gibberellic acid (GA 3 ) for 12 h could germinate in vitro on Murashige and Skoog medium (Nikam and Barmukh, 2009).…”
Section: Introductionmentioning
confidence: 99%